Perancangan Aplikasi Reba Solver Berbasis Sistem Operasi Android V 4.0.3 - Hutomo, Ricky; Iftadi, Irwan; Rosyidi, Cucuk Nur (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2013)
Most of the workers work without pay attention to their body posture. This is caused by lack ofknowledge and awareness about the importance of education. As result, health problem occurs among the workers that might causes injuries. Reba is one of the method that has been used to score/inspect body posture related to health problems among the workers. There are some steps to calculate Reba Score such as shooting stage, stage of determining the angles of worker posture, weight determination, and data processing Reba .Processing stage takes a long time because the user should see a table reference in calculating REBA score. Therefore we need a tool to calculate the Reba score. Designing tools to facilitate calculation REBA scores made on Android-based HP. As a result, when calculating scores Reba with the tools to save time 62% of the manual count